Association of dermatoses with duration and quantum of alcohol intake: A comparative cross-sectional study - Yugal Kishor Sharma; Pankaj Shukla; Roopa Nayak; Preeti Kothari; Aayush Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Chronic alcohol intake impacts skin directly, through organ dysfunction or by modifying preexisting dermatoses. However, dermatoses afflicting chronic alcoholics figure in a few studies only. Aim: This study aims to correlate the spectrum of dermatoses in chronic alcoholics with the quantum/duration of alcohol intake and raised liver transaminases. Materials and Methods: Adult males, totaling 196, ascertained to fulfill the Royal College of Psychiatry criteria for chronic alcoholism by the de-addiction center and referred for dermatological consult were enrolled as cases, and similar number of age-/sex-matched teetotallers, as controls. Data emanating from detailed history, clinical examination, and routine liver functions tests were summarized and subsequently analyzed, including statistically using the Chi-square, independent "t" and Spearman's rank correlation tests, and compared with data from previous studies. Results: Majority (104) drank 41-50 units of alcohol/week since 3-40 (mean: 20.01 ± 9.322) years. Generalized pruritus (odds ratio [OR]: 31.15, P < 0.001), xerosis (OR: 3.62, P = 0.008), and seborrheic dermatitis (OR: 12.26, P < 0.001) were significantly more common in cases than controls. Infections (73; 37.2%), eczemas (45; 22.9%), and generalized hyperpigmentation (28; 14.2%) were the major presenting complaints. Spider nevi, gynecomastia, and pellagroid dermatitis were present in 34 (17.3%), 19 (9.7%), and 8 (4.1%) respectively exclusively in cases only. Commonly seen systemic abnormalities were an alcoholic liver disease (45; 22.9%), diabetes mellitus (23; 11.7%), and peripheral neuropathy (19; 9.7%). Conclusion: Knowledge of cutaneous manifestations of chronic alcoholism could prompt in-depth history taking of alcohol intake, lead to specialist referral and thereby enable timely de-addiction, hopefully before serious adversities in the chronic alcoholics.